Saptapesona Literacy and Increasing Tourism Awareness in the Ciseupan Ecotourism Community, Cimahi City - Lukni Burhanuddin; Moch Vrans Romi; Nunung Aini Rahmah; Ferikawati Magdalena; Trisnia Manggiasih; Veronika Santi (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
Ecotourism plays a vital role in preserving natural habitats and biodiversity while promoting sustainable management practices through energy efficiency, waste management, and environmental awareness. This community service initiative, conducted in the Ciseupan area of Cimahi City, aimed to enhance local understanding of the Sapta Pesona concept—safety, orderliness, cleanliness, coolness, beauty, friendliness, and memorable experiences—to support the sustainable development of ecotourism. The methodology involved problem identification with Pokdarwis Cibeber, workshops, focus group discussions (FGD), and evaluations. Primary data were collected through FGDs with 19 purposively sampled participants, while secondary data were derived from government reports and tourism management documents. Results revealed varied levels of public understanding of Sapta Pesona, with significant improvements in awareness among participants involved in the program. However, challenges such as limited program reach and inadequate public facilities were identified. Strategic recommendations include expanding educational outreach, providing specialized training, improving infrastructure, and fostering multisector collaboration. The initiative demonstrated a positive impact by raising awareness of tourism's ecological and economic benefits, laying the groundwork for sustainable ecotourism development in Ciseupan.